2015
DOI: 10.1007/s10936-015-9349-3
|View full text |Cite
|
Sign up to set email alerts
|

Morphological Decomposition in Japanese De-adjectival Nominals: Masked and Overt Priming Evidence

Abstract: Whether morpheme-based processing extends to relatively unproductive derived words remains a matter of debate. Although whole-word storage and access has been proposed for some derived words, such as Japanese de-adjectival nominals with the unproductive (-mi) suffix (e.g., Hagiwara et al. in Language 75:739-763, 1999), Clahsen and Ikemoto (Ment Lex 7:147-182, 2012) found masked priming from de-adjectival nominals with productive (-sa) and unproductive (-mi) suffixes to their adjectivally-inflected base morphem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 44 publications
0
11
0
Order By: Relevance
“…Similarly, a number of masked priming studies have investigated morphological phenomena in other Indo-European languages such as German (derivation: Mousikou & Schroeder, 2019;inflection: Neubauer & Clahsen, 2009), Dutch (Diependaele, Sandra, & Grainger, 2009), French (derivation: Giraudo & Grainger, 2000;inflection: Meunier & Marslen-Wilson, 2004), Spanish (Domínguez, Cuetos, & Segui, 2000;Domínguez, Segui, & Cuetos, 2002), and Russian (Kazanina, Dukova-Zheleva, Geber, Kharlamov, & Tonciulescu, 2008). Lastly, there are also some masked priming studies investigating morphological decomposition in non-Indo-European languages, such as Basque (Duñabeitia, Laka, Perea, & Carreiras, 2009), Japanese (Clahsen & Ikemoto, 2012;Fiorentino, Naito-Billen, & Minai, 2016), Korean (Kim, Wang, & Taft, 2015), and Turkish (Kirkici & Clahsen, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, a number of masked priming studies have investigated morphological phenomena in other Indo-European languages such as German (derivation: Mousikou & Schroeder, 2019;inflection: Neubauer & Clahsen, 2009), Dutch (Diependaele, Sandra, & Grainger, 2009), French (derivation: Giraudo & Grainger, 2000;inflection: Meunier & Marslen-Wilson, 2004), Spanish (Domínguez, Cuetos, & Segui, 2000;Domínguez, Segui, & Cuetos, 2002), and Russian (Kazanina, Dukova-Zheleva, Geber, Kharlamov, & Tonciulescu, 2008). Lastly, there are also some masked priming studies investigating morphological decomposition in non-Indo-European languages, such as Basque (Duñabeitia, Laka, Perea, & Carreiras, 2009), Japanese (Clahsen & Ikemoto, 2012;Fiorentino, Naito-Billen, & Minai, 2016), Korean (Kim, Wang, & Taft, 2015), and Turkish (Kirkici & Clahsen, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Making use of masked or overt priming paradigms, Clahsen and Ikemoto (2012), Fiorentino, Naito-Billen, and Minai (2016), and Silva and Clahsen (2008) have shown that the effect of productivity might not be a good predictor of decomposability for derivational affixes. It should be noted, however, that the above studies focused on the very early processing of morphologically complex word forms and that their results should not be taken as directly relevant to the findings of the present study and other studies that have relied on off-line measures.…”
Section: Resultsmentioning
confidence: 99%
“…Japanese). In previous research, priming effects under masked stimulus conditions have been reported for morphologically complex words in Japanese (Clahsen and Ikemoto, 2012 ; Fiorentino et al, 2015 ), specifically for deadjectival forms with the suffixes – sa and – mi . In both studies, significant masked priming effects were found irrespective of whether primes and targets were spelled in the common mixed script (i.e., with kanji plus kana) or in kana only.…”
Section: The Present Studymentioning
confidence: 87%
“…Consequently it is conceivable that the reported priming effects are due to this overlap in kanji, rather than (or perhaps on top of) affix stripping. Consider, for example, the prime-target pair 楽しい - 楽しみ “delightful-delightfulness” from Fiorentino et al ( 2015 , Table 1 ) from which the orthographic overlap in terms of shared kanji is obvious. Clahsen and Ikemoto ( 2012 ) tried to reduce this kind of direct orthographic overlap between primes and targets by presenting their stimuli in the kana-only script, with the primes and the targets in hiragana.…”
Section: The Present Studymentioning
confidence: 99%
See 1 more Smart Citation